Contemporary management and time to revascularization in upper extremity arterial injury. (April 2023) - Chipman, Amanda M; Ottochian, Marcus; Ricaurte, Daniel; Gunter, Grahya; DuBose, Joseph J; Stonko, David P; Feliciano, David V; Scalea, Thomas M; Morrison, Jonathan
Introduction: Upper extremity arterial injury is associated with significant morbidity and mortality for trauma patients, but there is a paucity of data to guide the clinician in the management of these injuries. The goals of this review were to characterize the demographics, presentation, clinical management, and outcomes, and to evaluate how time to intervention associates with outcomes in trauma patients with upper extremity vascular injuries. Methods: The National Trauma Data Bank (NTDB) Research Data Set for the years 2007–2016 was queried in order to identify adult patients (age ≥ 18) with an upper extremity arterial injury. Patients with brachiocephalic, subclavian, axillary, or brachial artery injury using the 1998 and 2005 versions of the Abbreviated Injury Scale were included. Patients with non-survivable injuries to the brain, traumatic amputation, or other major arterial injuries to the torso or lower extremities were excluded. Results: The data from 7908 patients with upper extremity arterial injuries was reviewed. Of those, 5407 (68.4%) underwent repair of the injured artery. The median Injury Severity Score (ISS) was 10 (IQR = 7–18), and 7.7% of patients had a severe ISS (≥ 25). Median time to repair was 120 min (IQR = 60–240 min). Management was open repair in 52.3%, endovascular repair in 7.3%, and combined open and endovascular repairs in 8.8%; amputation occurred in 1.8% and non-operative management was used in 31.6% of patients. Blunt mechanism of injury, crush injury, concomitant fractures/dislocations, and nerve injuries were associated with amputation, whereas simultaneous venous injury was not. There was a significant decrease in the rate of amputation when patients undergoing surgical revascularization did so within 90 min of injury (P = 0.007). Conclusion: Injuries to arteries of the upper extremity are managed with open repair, endovascular repair, and, rarely, amputation. Expeditious transport to the operating room for revascularization is the key for limb salvage.